2019
DOI: 10.3390/genes10060424
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Farming Practices on Agricultural Soil Microbiome Members Represented by Metagenomically Assembled Genomes (MAGs) and Their Predicted Plant-Beneficial Genes

Abstract: To follow the hypothesis that agricultural management practices affect structure and function of the soil microbiome regarding soil health and plant-beneficial traits, high-throughput (HT) metagenome analyses were performed on Chernozem soil samples from a long-term field experiment designated LTE-1 carried out at Bernburg-Strenzfeld (Saxony-Anhalt, Germany). Metagenomic DNA was extracted from soil samples representing the following treatments: (i) plough tillage with standard nitrogen fertilization and use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 125 publications
1
25
0
Order By: Relevance
“…Recently, the inner mechanisms of intercropping are found related to microorganisms [25]. The progress in molecular [26] and microbiome techniques [27] provided new tools for the elucidation of the mechanisms of intercropping. For instance, molecular mechanisms of microbial disease control in intercropping were related to signals triggered by neighboring plants [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the inner mechanisms of intercropping are found related to microorganisms [25]. The progress in molecular [26] and microbiome techniques [27] provided new tools for the elucidation of the mechanisms of intercropping. For instance, molecular mechanisms of microbial disease control in intercropping were related to signals triggered by neighboring plants [28].…”
Section: Introductionmentioning
confidence: 99%
“…Although all cultivated AOA strains grow chemolithoautotrophically through oxidation of ammonia, several studies have suggested that growth of at least some AOA predominant in soils and freshwater might not depend solely, or primarily, on ammonia oxidation (see for example Jia and Conrad, 2009; Xu et al, 2012; Alves et al, 2018; Nelkner et al, 2019 for overview). Incorporation of carbon from organic substrates into AOA cells has also been reported in ocean waters (Ouverney and Fuhrman, 2000; Ingalls et al, 2006; Hansman et al, 2009), and other studies were unable to detect autotrophic carbon assimilation in populations actively growing in wastewater treatment plants (Mussmann et al, 2011; Sauder et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study of the effect of agricultural management practices on crop soil microbial communities is also a growing field for the use of shotgun metagenomics and aims to correlate these practices to microbial community taxonomic diversity and the pool of functions (Souza et al, 2018;Nelkner et al, 2019). In their study, Souza et al (2018) analyzed soil samples that were subjected to four different soil and crop management practices (conventional tillage and no tillage, each with crop succession or crop rotation).…”
Section: Metagenomicsmentioning
confidence: 99%